Sustainable manufacturing : concepts, tools, methods, and case studies - Vinodh, S. (Boca Raton, FL : CRC Press, 2020)
Sustainability enables the development of products with minimal environment impact coupled with economical and societal benefits. This book provides an understanding of theoretical and practical perspectives pertaining to Sustainable manufacturing. This book focuses on fundamentals, providing insights, concepts, tools, methods, case studies, and practical perspectives taken from research. The book will be of interest to students, researchers and industry practitioners.
1. Concepts and Fundamentals of Sustainable Manufacturing, Triple Bottom Line Approach. 2. Sustainable Manufacturing Tools -- Environmental Conscious QFD. 3. Sustainable Manufacturing Tools -- Life Cycle Assessment (LCA). 4. Life Cycle Impact Assessment Methods -- CML, EI95, EI99 Methods. 5. Design Strategies Supporting Sustainable Manufacturing. 7. Product Sustainability and Risk/benefit Assessment & Corporate Social Responsibility. 8. Sustainability Assessment.9. Software Modules for LCA & Sustainable Manufacturing. 10. Sustainability and Energy Efficiency of Manufacturing Processes. 11. Case Studies on ECQFD, LCA, MCDM. 12. Research Issues in Sustainable Manufacturing.
OCLC-licensed vendor bibliographic record.
Keywords: Manufacturing processes -- Environmental aspects; Lean manufacturing; Sustainable engineering; TECHNOLOGY / Manufacturing; TECHNOLOGY / Industrial Design / Product